Welding metallurgy of martensitic advanced high strength steels during resistance spot welding. (19th May 2017) - Tamizi, M.; Pouranvari, M.; Movahedi, M.
ABSTRACT: The paper addresses the process–microstructure–performance relationships in resistance spot welding of a martensitic advanced high strength steel. Significant softening was observed in the heat affected zone (HAZ) due to allotriomorphic ferrite formation in the inter-critical HAZ and tempering of martensite in sub-critical HAZ (SCHAZ), with the latter plays more important role in mechanical properties of the spot welds. The strain concentration associated with the HAZ softening promotes initiation of pullout failure from the soft SCHAZ. While, the peak load in the interfacial failure mode is governed by the fusion zone size, that of the pullout mode is significantly affected by the HAZ softening. To improve weldability of martensitic steels, the HAZ softening should be minimised via modifications in welding process or steel chemistry.